Mental fatigue increases across a 16-week pre-season in elite female athletes - Russell, S.; Jenkins, D. G.; Halson, S. L.; Kelly, V. G. (Journal of Science and Medicine in Sport, 2022)
Objectives: To examine potential changes in mental and physical fatigue across an elite netball pre-season training phase and relationships between mental fatigue, physical fatigue, salivary cortisol (sCort) and alpha-amylase (sAA). Design: Observational with repeated measures. Methods: Across a 16-week pre-season, 10 elite female netballers (25.3 +- 3.7y) rated their physical fatigue, mental fatigue and readiness to perform on 100-mm visual analogue scales, and provided salivary samples for sCort and sAA analyses. Results: Linear mixed model analyses revealed elevated (p < 0.05) ratings of mental fatigue for weeks 12, 14 and 15 v 1; 12, 14 and 15 v 4 and 14 v 7. Higher (p < 0.05) ratings of physical fatigue were reported on weeks 6, 10, 11 and 12-16 compared to week 4; and 10 and 13 compared to week 7. Moderate and large ES differences were found between multiple weeks. Mental and physical fatigue demonstrated a shared variance of 14.3% (r = 0.38, p < 0.001) and an inverse relationship was observed between mental fatigue and readiness to perform (r = 0.50; p < 0.001). Changes in sCort nor sAA were not related to changes in mental or physical fatigue. Conclusions: Mental fatigue fluctuated across the 16-week pre-season phase with elevated ratings observed in the later weeks. Whilst value remains in identifying subjective tools to assess mental fatigue; salivary biomarkers do not appear to be a suitable objective indicator of mental fatigue in the applied sporting environment. Practitioners should work to identify and manage mental fatigue with the same level of importance given to the periodisation of physical fatigue.; ObjectivesTo examine potential changes in mental and physical fatigue across an elite netball pre-season training phase and relationships between mental fatigue, physical fatigue, salivary cortisol (sCort) and alpha-amylase (sAA).